2017
DOI: 10.1016/j.msksp.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The development of the Dutch version of the Fremantle Back Awareness Questionnaire

Abstract: Background: Disturbed body perception may play a role in the aetiology of chronic low back pain (LBP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 64 publications
9
53
4
Order By: Relevance
“…We found that people with CP and LBP endorsed questionnaire items related to distorted body image more frequently than people with CP who do not report LBP. Furthermore, the score on the FreBAQ questionnaire in the CP_Pain population was no different from that seen in a matched group with LBP and no CP and very similar to the results of previous investigations that have used the FreBAQ to assess body perception in general LBP populations . This builds on work demonstrating that lumbopelvic self‐perception is impaired in people with LBP compared to matched control groups and extends this finding to include people with LBP and CP.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We found that people with CP and LBP endorsed questionnaire items related to distorted body image more frequently than people with CP who do not report LBP. Furthermore, the score on the FreBAQ questionnaire in the CP_Pain population was no different from that seen in a matched group with LBP and no CP and very similar to the results of previous investigations that have used the FreBAQ to assess body perception in general LBP populations . This builds on work demonstrating that lumbopelvic self‐perception is impaired in people with LBP compared to matched control groups and extends this finding to include people with LBP and CP.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the score on the FreBAQ questionnaire in the CP_Pain population was no different from that seen in a matched group with LBP and no CP and very similar to the results of previous investigations that have used the FreBAQ to assess body perception in general LBP populations. 15,23,25,26 This builds on work demonstrating that lumbopelvic self-perception is impaired in people with LBP compared to matched control groups 23,24,26,59,60 and extends this finding to include people with LBP and CP. We were also interested in investigating the confounding effect that postural and motor impairments might have on self-perception of the back in the CP population.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A graphical distribution of included studies grouped by clinical conditions examined is shown in Figure 3. Twenty-five studies (Grod and Diakow, 2002;Moseley, 2008;Wand et al, 2010Wand et al, , 2013bWand et al, , 2014Wand et al, , 2016Docherty et al, 2012;Lauche et al, 2012a;Valenzuela-Moguillansky, 2013;Hirakawa et al, 2014;Gilpin et al, 2015;Mibu et al, 2015;Nishigami et al, 2015Nishigami et al, , 2017Nishigami et al, , 2018Treleaven and Takasaki, 2015;Beales et al, 2016;Janssens et al, 2017;Moreira et al, 2017;Adamczyk et al, 2018a,b;Ehrenbrusthoff et al, 2018;Magni et al, 2018;Martínez et al, 2018) studies concerned the assessment of SoP dysfunctions, while twelve interventional studies (Barker et al, 2008;Preston and Newport, 2011;Wand et al, 2011Wand et al, , 2013aMorone et al, 2012;Paolucci et al, 2012;Diers et al, 2013;Vetrano et al, 2013;Ryan et al, 2014;Louw et al, 2017;Stanton et al, 2018;Nishigami et al, 2019) investigated the effects of perception-based intervention to reduce pain or to correct perceptual distortions. One study, (Lauche et al, 2012a) was included both in assessment and in intervention studies: it is a qualitative study i...…”
Section: Study Selectionmentioning
confidence: 99%
“…The distribution of research designs adopted for assessment studies is graphically represented in Figure 5. A conspicuous number of these studies is composed by those validating the Fremantle Back Awareness Questionnaire (FreBAQ) (Wand et al, 2014) and the Fremantle Knee Awareness Questionnaire (FreKAQ) (Nishigami et al, 2017), including validation studies into other languages (Janssens et al, 2017;Ehrenbrusthoff et al, 2018;Nishigami et al, 2018), and cross-sectional or case-control investigations across different clinical samples (Wand et al, 2013aBeales et al, 2016). Figure 6 shows the research designs adopted in the intervention studies included, of which a large part were pre-clinical experimental studies (Diers et al, 2013;Nishigami et al, 2019).…”
Section: Research Designs Of Included Studiesmentioning
confidence: 99%